2005
DOI: 10.1038/sj.npp.1300692
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of THC and MDMA (‘Ecstasy’) Synergistically Disrupts Memory in Rats

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA, 'Ecstasy') and cannabis are two of the most commonly used illicit drugs in the western world, and are often used in combination. Very little research has examined their effect on cognitive function or behavior when combined. The present study used a double Y-maze task to examine the acute effect of MDMA and D 9 -tetrahydrocannabinol (THC, the principal psychoactive ingredient of cannabis) on mnemonic function in rats, at a range of doses representative of common human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Previous studies utilizing measures of accuracy often observed acute reductions of accuracy in working memory tasks (e.g. Braida et al, 2002; Galizio et al, 2009; Young, McGregor & Mallet, 2005), reference memory tasks (e.g. Kay et al, 2010), or both.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilizing measures of accuracy often observed acute reductions of accuracy in working memory tasks (e.g. Braida et al, 2002; Galizio et al, 2009; Young, McGregor & Mallet, 2005), reference memory tasks (e.g. Kay et al, 2010), or both.…”
Section: Discussionmentioning
confidence: 99%
“…Δ 9 ‐THC also undergoes additive or synergistic interactions in mice with nicotine for the production of conditioned place preference, hypothermia and hypolocomotion (Valjent et al. , 2002), with 3,4‐methylenedioxymethamphetamine (MDMA) in conditioned place preference, self‐administration and working memory paradigms (Young et al. , 2005; Robledo et al.…”
Section: Multi‐targetingmentioning
confidence: 99%
“…• reduction of nociceptive scratching behaviour induced in rats by injection of formalin into the temporomandibular joint Neither of these compounds displayed antinociceptive activity by itself and their ability to potentiate R-(+)-WIN55212 did not extend to the COX-1-selective inhibitor, SC-560. D 9 -THC also undergoes additive or synergistic interactions in mice with nicotine for the production of conditioned place preference, hypothermia and hypolocomotion (Valjent et al, 2002), with 3,4-methylenedioxymethamphetamine (MDMA) in conditioned place preference, self-administration and working memory paradigms (Young et al, 2005;Robledo et al, 2007) and, for the production of catalepsy or hypothermia in mice or rats, with a range of non-cannabinoids that in addition to opioids, nicotine, and MDMA include benzodiazepines, prostaglandins, reserpine and ligands that target muscarinic cholinoceptors or some types of dopamine, noradrenaline, 5-hydroxytryptamine or g-aminobutyric acid receptors as agonists or antagonists (Marchese et al, 2003;review by Pertwee, 1992).…”
Section: Cannabinoid Receptor Agonistmentioning
confidence: 99%
“…Two previous studies reported on the effects of acute co-administration of THC and MDMA in adult rats (Morley et al , 2004; Young et al , 2005), and more recently Robledo and coworkers (2007) examined both the acute neurochemical effects of THC and MDMA co-administration and the combined effects of these compounds in a conditioned place paradigm in mice. However, to our knowledge there is no published information regarding the consequences of recurrent adolescent co-administration of these compounds in a rodent model.…”
Section: Introductionmentioning
confidence: 99%